Advanced Transmission Electron Microscopy : Imaging and Diffraction in Nanoscience - Zuo, Jian Min; Spence, John C.H (Springer New York : Imprint: Springer, 2017)
This volume expands and updates the coverage in the authors' classic 1992 book, "Electron Microdiffraction." As the title implies, the focus of the book has changed from electron microdiffraction, or convergent beam electron diffraction, to electron nanodiffraction and the applications of electron diffraction from single crystals as well as general structure analysis of single crystals, powders, and nanostructures. Advanced Transmission Electron Microscopy provides a comprehensive treatment of theory and practice, and is written at a level suitable for advanced undergraduate students and graduate students and researchers in materials science, chemistry, and physics. Practical guides are provided for interpretation and simulation of electron diffraction patterns.- Resumé vydavatel
Keywords: transmisní elektronová mikroskopie; nanostruktury; nanotechnologie; nanochemie; transmission electron microscopy; nanostructures; nanotechnology; nanochemistry; elektronické knihy; monografie; electronic books; monographs